2016
DOI: 10.1002/adhm.201600684
|View full text |Cite
|
Sign up to set email alerts
|

Culture on 3D Chitosan‐Hyaluronic Acid Scaffolds Enhances Stem Cell Marker Expression and Drug Resistance in Human Glioblastoma Cancer Stem Cells

Abstract: The lack of in vitro models that support the growth of glioblastoma (GBM) cancer stem cells (GSCs) that underlie clinical aggressiveness hinders developing new, effective therapies for GBM. While orthotopic patient-derived xenograft models of GBM best reflect in vivo tumor behavior, establishing xenografts is a time consuming, costly and frequently unsuccessful endeavor. To address these limitations, we synthesize a three-dimensional porous scaffold composed of chitosan and hyaluronic acid (CHA), and compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 53 publications
3
59
0
Order By: Relevance
“…For instance,Todaro et al (2007) produced spheroids with cells obtained from human colon adenocarcinoma tissue fragments and confirmed the expression of a CSC marker, that is, CD133. Other studies showed that the spheroids produced with CSC obtained from cancer cell lines (e.g., BT-474, GBM6, H1650, and MDA-MB-231) demonstrated a higher resistance toward different therapeutics (e.g., 5-FU, camptothecin, carmustine, cisplatin, gemcitabine, lomustine, paclitaxel, temozolomide, and trastuzumab) than 2D cell cultures(Godugu et al, 2013;Reynolds et al, 2017;Rodríguez et al, 2018;K. For example, the 100 µM of oxaliplatin reduced the CD133+ cell viability in only almost equal to 10%, whereas the same treatment reduced the CD133− cell viability to almost equal to 70%(Todaro et al, 2007).Optionally, spheroids can be produced with CSC obtained from cancer cell lines (Figure 3).…”
mentioning
confidence: 99%
“…For instance,Todaro et al (2007) produced spheroids with cells obtained from human colon adenocarcinoma tissue fragments and confirmed the expression of a CSC marker, that is, CD133. Other studies showed that the spheroids produced with CSC obtained from cancer cell lines (e.g., BT-474, GBM6, H1650, and MDA-MB-231) demonstrated a higher resistance toward different therapeutics (e.g., 5-FU, camptothecin, carmustine, cisplatin, gemcitabine, lomustine, paclitaxel, temozolomide, and trastuzumab) than 2D cell cultures(Godugu et al, 2013;Reynolds et al, 2017;Rodríguez et al, 2018;K. For example, the 100 µM of oxaliplatin reduced the CD133+ cell viability in only almost equal to 10%, whereas the same treatment reduced the CD133− cell viability to almost equal to 70%(Todaro et al, 2007).Optionally, spheroids can be produced with CSC obtained from cancer cell lines (Figure 3).…”
mentioning
confidence: 99%
“…Glioblastoma (GBM6) cultured in CH scaffold showed enhanced stem cell marker expression resisted treatment of alkylating agents. [100] …”
Section: Spheroid Modelsmentioning
confidence: 99%
“…However, very few studies have employed 3D model systems to specifically study GSC behaviors (Nakod et al, ). Of these, majority of studies have utilized HA as an additive in conjunction with polycaprolactone (PCL; Martinez‐Ramos & Lebourg, ); chitosan (Florczyk et al, ; Wang et al, ); chitosan–alginate (Kievit et al, ); or collagen (Herrera‐Perez, Voytik‐Harbin, & Rickus, ); or as the base matrix incorporating synthetic polymers such as poly(ethylene glycol) (PEG; Xiao et al, ; Xiao et al, ). In addition, all of these studies, with the exception of a few (Herrera‐Perez et al, ; Xiao et al, ; Xiao et al, ), have utilized tumor cells grown in the presence of serum, which does not typically favor a stem‐like phenotype (Lee et al, ).…”
Section: Introductionmentioning
confidence: 99%